Lactobacillus plantarum CIDCA 8327: An α-glucan producing-strain isolated from kefir grains. (15th August 2017) - Gangoiti, M.V.; Puertas, A.I.; Hamet, M.F.; Peruzzo, P.J.; Llamas, M.G.; Medrano, M.; Prieto, A.; Dueñas, M.T.; Abraham, A.G.
Highlights: L. plantarum 8327 produces different EPS when grown in milk or semidefined medium. The EPS synthetized by L. plantarum 8327 grown in milk was characterized as an α-glucan. The glucan has a main chain with α-(1 → 4) glycosidic linkages branched at position O -3. This is the first report about glucan production in milk by Lactobacillus . Abstract: Lactobacillus plantarum CIDCA 8327 is an exopolysaccharide (EPS)-producer strain isolated from kefir with promising properties for the development of functional foods. The aim of the present study was to characterize the structure of the EPS synthesized by this strain grown in skim milk or semidefined medium (SDM). Additionally, genes involved in EPS synthesis were detected by PCR. L. plantarum produces an EPS with a molecular weight of 10 4  Da in both media. When grown in SDM produce an heteropolysaccharide composed mainly of glucose, glucosamine and rhamnose meanwhile the EPS produced in milk was composed exclusively of glucose indicating the influence of the sugar source. FTIR spectra of this EPS showed signals attributable to an α-glucan. Both by 1 H NMR and methylation analysis it was possible to determine that this polysaccharide is a branched α-(1 → 4)-d -glucan composed of 80% linear α-(1 → 4)-d -glucopyranosyl units and 19% (1 → 4)-d -glucopyranosyl units substituted at O-3 by single α-d -glucopyranosil residues.